Entrepreneurship Education and Nascent Entrepreneurship: A Qualitative Study - Donard Games; Dessy Kurnia Sari; Venny Darlis (Management Institute Faculty of Economics Universitas Andalas, 2019)
The objective of this research is to see whether entrepreneurship education and training really help nascent entrepreneurs particularly when they try to face the real business. Formal and non-formal entrepreneurship educations are commonly offered in Indonesia nowadays as entrepreneurship has become national campaign. Qualitative approach is used in this research. Multiple case studies methods are used to discover the relationship between entrepreneurship education and the success of nascent entrepreneurs in SMEs development. We asked young entrepreneurs, who were nascent entrepreneurs in West Sumatera-a province in Indonesia. We asked them about the effectiveness of entrepreneurship training and education in determining their success as entrepreneurs. We found that education has contributed positively in terms of motivation, but less benefit in technical ability and practical aspect in business world. These young entrepreneurs define their achievement now as “small win” which can lead them to the next level of success as entrepreneurs.